MARKETING SIMULATIONS IN BUSINESS EDUCATION - ȘTEFAN-ALEXANDRU CATANĂ; SORIN-GEORGE TOMA; CĂTĂLIN GRĂDINARU (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2022)
Marketing simulations is an important topic in business education, as it aims to connect theory with practice and help students and marketing specialists become familiar with the marketing activities carried out in a company. This article presents the basic theoretical concepts of marketing simulations topic and their influence on business education. The research methodology was based on a quantitative research method. The paper contributes to the deepening of the theoretical framework to better understand the marketing simulations field. It also shows that marketing simulations allow for the development of higher learning skills and knowledge compared to more traditional assessments. The paper facilitates a better understanding of the concept of marketing simulations.